Development of an all-sky camera for short-term forecasting of photovoltaic generation - Santisi, Sebastián (2023)
In photovoltaic solar generation, the intensity of solar radiation directly influences the power generated. The radiation is strongly affected by the presence of clouds, which modify it quickly and intermittently. In order to take control and management decisions for a photovoltaic installation, it would be desirable to have the ability of predicting the generation drop events. Among the different types of forecast available, the forecast using all-sky cameras is the only one capable of predicting the evolution of clouds based on local observation of the sky, allowing the events of the next few minutes to be anticipated. In this article we show the development of an all-sky camera prototype which covered both the design of the hardware and the procedure necessary to forecast the evolution of cloud cover, as well as its representation in software.